PHONOLOGICAL INTEGRATION OF MINANGKABAU LANGUAGE WITH BENGKULU MALAY LANGUAGE IN THE LYRICS OF THE BENGKULU LOCAL SONG “IKAN PAIS” - Harmia, Citra Dewi (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
This article aims to describe the phenomenon of phonological integration of the Minangkabau language in Bengkulu Malay which is contained in the lyrics of the Bengkulu’s traditional song entitled "Ikan Pais". The theory used to analyze phonological integration in this article is Terry Crowley's (1997) generative phonology theory. The types of sound changes that appear in this analysis are grouped into three types of sound changes, namely; (1) Addition of sounds (2) Deletion of sounds, (3) Change of sounds. The research method used in this article is a descriptive-qualitative method. The main data used in this study were taken from the lyrics of the song "Ikan Pais" written in Bengkulu Malay. Data were collected from the vocabulary contained in the song lyrics which were then analyzed using the two-language equivalence method and the technique of equalizing and differentiating comparisons. The results of the analysis in this study show the form of phonological integration of the Minangkabau language in three phoneme phenomena; addition of phonemes, removal of phonemes, and changes in phonemes.